Risk factors for therapy failure after incision and drainage alone for perianal abscesses in children - Ding, CaiLin; Chen, YaJun; Yan, JiaYu; Wang, Kai; Tan, Sarah Siyin (Frontiers in Pediatrics, 2024)
Background It is well known that recurrent perianal abscesses (PAs) and fistula-in-ano (FIA) are the main causes of therapy failure following incision and drainage (I&D) for PAs. But few studies have focused on the risk factors for therapy failure after I&D for PAs in children. In this study, we retrospectively examine the risk factors for therapy failure after I&D for PAs in children in a pediatric tertiary care institution. Methods A retrospective review of all outpatient children with PA treated by I&D at Beijing Children's Hospital between January 2021 and December 2022 was performed. A follow-up was conducted in October 2023. Patients with other predisposing factors for perianal infection, such as inflammatory bowel disease, hematologic tumor, and anorectal surgery, were excluded from this study. Logistic regression yielding odds ratios (ORs) was used to assess the significance of variables for therapy failure. Results Of 160 children initially identified, follow-up was available for 146, with a total of 172 treatments. A total of 91% of children were male. The median (interquartile range) age at I&D was 2 (1, 15) months. The median follow-up duration was 20 (14, 25) months. Therapy failure occurred in 25 (15%) treatments performed for the prevention of recurrence of PA and in 35 (20%) treatments for the prevention of development of FIA. In the univariate analysis, a history of PA (P = 0.001), history of I&D (P = 0.014), and multilocal occurrence (P = 0.003) were associated with therapy failure. A sitz bath after I&D (P = 0.016) and regular cleaning of the wound after I&D (P = 0.024) were associated with therapy success. In the multivariate analysis, a history of PA (P = 0.015, OR = 3.374) and multilocal occurrence (P = 0.012, OR = 4.649) were independently associated with therapy failure. Regular cleaning of the wound (P = 0.017, OR = 0.341) and sitz bath (P = 0.001, OR = 0.128) after I&D were independently associated with therapy success. Conclusions A history of PA and multilocal occurrence were predictor factors for therapy failure before I&D. Regular cleaning of the wound and sitz bath after I&D were protective factors for therapy success. Therefore, regular cleaning of the wound and sitz bath after I&D should be emphasized in all children with PAs, especially in those with a history of PA and multilocal occurrence.